Therapeutic Effect of Pericytes for Diabetic Wound Healing - Kim, Kyeong Mi; An, Hyun-Ju; Kim, Sang-Hoon; Kim, JuHee; Sim, Changgon; Lee, Jaemin; Park, Sin Hyung; Lee, Hyun Il; Jang, Inseok; Lee, Soonchul (Frontiers in Cardiovascular Medicine, 2022)
Objective: Numerous attempts have been made to devise treatments for ischemic foot ulcer (IFU), which is one of the most severe and fatal consequence of diabetes mellitus (DM). Pericytes, which are perivascular multipotent cells, are of interest as a treatment option for IFU because they play a critical role in forming and repairing various tissues. In this study, we want to clarify the angiogenic potential of pericytes in DM-induced wounds. Methods: We evaluated pericyte stimulation capability for tube formation, angiogenesis, and wound healing (cell migration) in human microvascular endothelial cells (HUVEC) with in vivo and in vitro models of high glucose conditions. Results: When HUVEC were co-cultured with pericytes, their tube forming capacity and cell migration were enhanced. Our diabetic mouse model showed that pericytes promote wound healing via increased vascularization. Conclusions: The findings of our study indicate that pericytes may enhance wound healing in high glucose conditions, consequently making pericyte transplantation suitable for treating IFUs.